Pelatihan Membuat Advertorial di Industri Periklanan Pada Siswa Kelas 10 Jurusan Broadcasting SMK Negeri 1 Semarang - Rizkika Voni Riyati; Luthfiya Yuninda Purwanti; Icel Gavril Praditta; Rendy Ray Ismahendra; Rayhan Bimantoro; Ayu Aliviana (Institut Nalanda, 2024)
Training on Creating Advertorials in the Advertising Industry is a study that aims to identify the effectiveness of training in developing the skills of class 10 students majoring in Broadcasting at SMK Negeri 1 Semarang in creating advertorials. Advertorials are a form of advertising that combines editorial elements with the promotion of certain products or services. The training method used is a hands-on practical approach, where students are given theoretical knowledge about the basic principles of creating advertorials and then apply it in practical exercises. This training includes an introduction to advertising concepts, target audience analysis, writing advertorial scripts, and effective use of visual elements. A total of 70 10th grade students majoring in Broadcasting were involved in this research. Data was collected through written tests before and after training, as well as practical performance assessments conducted by training instructors. The research results showed that there was a significant increase in students' knowledge about creating advertorials after attending the training. Apart from that, the practical performance assessment also showed an increase in students' ability to produce good advertorials in terms of content and visual presentation. This research shows that training is an effective method in introducing and teaching advertorial creation skills to students majoring in Broadcasting. With this training, students can develop skills relevant to the advertising industry and improve their future career prospects.